2017
DOI: 10.1289/ehp634
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to Climate Change: A Comparative Analysis of Modeling Methods for Heat-Related Mortality

Abstract: Background:Multiple methods are employed for modeling adaptation when projecting the impact of climate change on heat-related mortality. The sensitivity of impacts to each is unknown because they have never been systematically compared. In addition, little is known about the relative sensitivity of impacts to “adaptation uncertainty” (i.e., the inclusion/exclusion of adaptation modeling) relative to using multiple climate models and emissions scenarios.Objectives:This study had three aims: a) Compare the range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(95 citation statements)
references
References 58 publications
2
82
0
1
Order By: Relevance
“…Other studies using a range of methods have reported a reduction by between 20% and 80% in future impacts under various adaptation assumptions [50,52,53]. A recent comprehensive analysis in 14 European cities applied six different adaptation assumptions for future projections, and concluded that uncertainties related to adaptation were generally larger than those related to climate models and emission scenarios [54].…”
Section: Projecting Future Temperature Effectsmentioning
confidence: 99%
“…Other studies using a range of methods have reported a reduction by between 20% and 80% in future impacts under various adaptation assumptions [50,52,53]. A recent comprehensive analysis in 14 European cities applied six different adaptation assumptions for future projections, and concluded that uncertainties related to adaptation were generally larger than those related to climate models and emission scenarios [54].…”
Section: Projecting Future Temperature Effectsmentioning
confidence: 99%
“…For the projected change in heat related mortality, long-term adaptation needs to be considered [42,43] and several different methods exists, to assess long-term adaptation to heat stress for the future [44]. Estimates of long-term adaption for long-lasting heat waves, however, are associated with large uncertainties, given the fact that heat waves with a duration of more than 5 days occured only once or less during the reference period.…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted worldwide indicates that public health consequences associated with cyclones can include: infectious diseases, psycho-social effects, displacement, damage to healthcare infrastructure, disruption of public health services, transformation of ecosystems, social dislocation, loss of jobs and livelihoods and economic crisis (Shultz et al, 2005). One of the major direct public health risks imposed by climate change is increased heat-related mortality and morbidity (Gosling et al, 2017;Hajat, Vardoulakis, Heaviside, & Eggen, 2014). This is a major concern for Asian megacities such as Dhaka, the capital of Bangladesh (Kovats & Akhtar, 2008).…”
Section: Direct Effectsmentioning
confidence: 99%